A Study Of Corrosion Of Steels In Carbon Dioxide And Sulphide Solutions - Taher, Abualmaali M. Y. (1993)
The present investigation has been successful in resolving the controversy about CO2 corrosion of mild steel and 13% Cr martensitic stainless steel in brine solution with and without sulphur content. It has been observed that the corrosion behaviour of mild steel and 13% Cr stainless steel depends on the combination of CO2 pressure and sulphur content. The corrosion rate may increase or decrease depending upon a particular combination.